2020
DOI: 10.1177/0706743720936462
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adherence to Responsible Reporting of Suicide Guidelines in the Canadian News Media: A 1-year Examination of Day-to-day Suicide Coverage: Évaluer la conformité au journalisme responsable en matière de directives sur le suicide dans les médias canadiens d’information: Un examen d’une année de la couverture quotidienne du suicide

Abstract: Objective: This study aims to examine routine day-to-day suicide reporting in the Canadian media, giving a descriptive overview of the tone and content of news articles. The primary objective is to assess adherence to responsible reporting of suicide recommendations in news articles about suicide. A secondary objective is to categorize these articles according to their focus. A tertiary objective is to compare guideline adherence across the different categories of articles. Methods: We collected news articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
(83 reference statements)
0
5
1
Order By: Relevance
“…We found that, postimplementation, the national initiative was associated with substantial reductions in putatively harmful content and across-the-board increases in the proportion of articles with putatively protective content, a finding aligned with other recent Canadian research on media and suicide. [34][35][36] This finding differs somewhat from what we observed immediately after the release of the Mindset Guidelines and following the combined initiative onset. The release and dissemination of Mindset Guidelines coincided with some positive changes that appeared to persist over time (e.g., a greater proportion of articles presenting alternatives to suicide), but also negative changes that persisted for some years (e.g., a greater proportion of articles describing suicide methods in detail, presenting simplistic reasons for suicide).…”
Section: Discussioncontrasting
confidence: 99%
“…We found that, postimplementation, the national initiative was associated with substantial reductions in putatively harmful content and across-the-board increases in the proportion of articles with putatively protective content, a finding aligned with other recent Canadian research on media and suicide. [34][35][36] This finding differs somewhat from what we observed immediately after the release of the Mindset Guidelines and following the combined initiative onset. The release and dissemination of Mindset Guidelines coincided with some positive changes that appeared to persist over time (e.g., a greater proportion of articles presenting alternatives to suicide), but also negative changes that persisted for some years (e.g., a greater proportion of articles describing suicide methods in detail, presenting simplistic reasons for suicide).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, in an evaluation of 243 media articles reporting on two high profile cases of suicide, nearly all the articles (99%) breached at least one guideline recommendation and more than half breached three or more recommendations [ 34 ]. Better adherence was found in analyses of Australian and Canadian media, with most articles omitting the word suicide in the headlines and the suicide method in the text [ 18 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following a review of the scientific literature, it can be determined that certain media interventions may become risk factors for suicidal behaviour. With regard to the placement of news about suicide, the Canadian Psychiatric Association and the Canadian Association for Suicide Prevention state that news about suicidal behaviour should not be displayed on the front page of newspapers or on the back page, should avoid sensationalism, should not provide details about the site/location, should not explicitly describe the medium used, should not use photographs, video footage or social media links, and should not repeat the news story unduly [35,36]. This is in line with WHO recommendations, which has worked on several manuals to approach this issue [17,37,38].…”
Section: Discussionmentioning
confidence: 99%